The Relationship between Metabolic Syndrome and Shift Work in Midwives: A Cross Sectional Study - Karami, Azadeh; Amir Ali Akbari, Sedigheh; Nasiri, Maliheh; Hadaegh, Farzad (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Recent studies suggest that shift work can be associated with the incidence of metabolic syndrome. The present study was conducted in 2019 to investigate the relationship between metabolic syndrome and shift work in midwives working in hospitals affiliated to universities of medical sciences in Tehran, Iran. Methods: The present analytical cross-sectional study recruited 216 midwives who satisfied the inclusion criteria. Questionnaires were first used to collect demographic information and job records. Waist circumference and blood pressure of the subjects were then measured. A 12-hour fasting blood test was performed to determine fasting blood sugar (FBS), triglyceride and HDL levels. The frequency of metabolic syndrome was ultimately evaluated based on the Harmonized criteria. Data were analyzed in SPSS using the Chi-square and Fisher's exact tests. Results: The prevalence of metabolic syndrome was found to be 6.9% in the midwives using the Harmonized criteria. Although the prevalence of metabolic syndrome was higher in the night-shift workers (11.5%) compared to that in the other two groups, but the difference was not significant. Low HDL cholesterol and abdominal obesity were respectively the most frequent metabolic syndrome criteria. Significant relationships were observed between low HDL cholesterol and night shift (P<0.001), and also between abdominal obesity and rotational shift work (P<0.001). Conclusions: According to the present findings, a higher prevalence of metabolic syndrome was observed in the night-shift workers, and rotational shift work was found to be significantly associated with two of the metabolic syndrome criteria, namely low HDL levels and abdominal obesity.